Evaluating lower limb tendinopathy with Victorian Institute of Sport Assessment (VISA) questionnaires: a systematic review shows very-low-quality evidence for their content and structural validity—part I - Vasileios Korakakis (5069123) (2021)
Purpose The Victorian Institute of Sport Assessment (Achilles tendon—VISA-A, greater trochanteric pain syndrome—VISA-G, proximal hamstring tendinopathy—VISA-H, patellar tendon—VISA-P) questionnaires are widely used in research and clinical practice; however, no systematic reviews have formally evaluated their content, structural, and cross-cultural validity evidence. The measurement properties referring to content, structural and cross-cultural validity of the VISA questionnaires were appraised and synthesized. Methods The systematic review was conducted according to Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) methodology. PubMed, Cochrane, CINAHL, EMBASE, Web of Science, SportsDiscus, grey literature, and reference lists were searched. Development studies and cross-cultural adaptations (12 languages) assessing content or structural validity of the VISA questionnaires were included and two reviewers assessed their methodological quality. Evidence for content (relevance, comprehensiveness, and comprehensibility), structural, and cross-cultural validity was synthesized. A modified Grading of Recommendations Assessment Development and Evaluation (GRADE) approach was applied to evidence synthesis. Results The VISA-A presented very-low-quality evidence of sufficient relevance, insufficient comprehensiveness, and inconsistent comprehensibility. VISA-G displayed moderate-quality evidence for sufficient comprehensibility and very-low-quality evidence of sufficient relevance and comprehensiveness. The VISA-P presented very-low-quality evidence of sufficient relevance, insufficient comprehensiveness, and inconsistent comprehensibility, while VISA-H presented very-low evidence of insufficient content validity. VISA-A displayed low-quality evidence for structural validity concerning unidimensionality and internal structure, while VISA-H presented low-quality evidence of insufficient unidimensionality. The structural validity of VISA-G and VISA-P were indeterminate and inconsistent, respectively. Internal consistency for VISA-G, VISA-H, and VISA-P was indeterminate. No studies evaluated cross-cultural validity, while measurement invariance across sexes was assessed in one study. Conclusions Only very-low-quality evidence exists for the content and structural validity of VISA questionnaires when assessing the severity of symptoms and disability in patients with lower limb tendinopathies. Level of evidence IV. Registration PROSPERO reference—CRD42019126595. Other Information Published in: Knee Surgery, Sports Traumatology, Arthroscopy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00167-021-06598-5